Electroencephalogram patterns in critical care: A primer for acute care doctors. (February 2022) - Anderson, Dustin; Jirsch, Jeffrey D; Wheatley, Matt B; Brindley, Peter G
Electroencephalograms are commonly ordered by acute care doctors but not always understood. Other reviews have covered when and how to perform electroencephalograms. This primer has a different, unique, and complementary goal. We review basic electroencephalogram interpretation and terminology for nonexperts. Our goal is to encourage common understanding, facilitate inter specialty collaboration, dispel common misunderstandings, and inform the current and future use of this precious resource. This primer is categorically not to replace the expert neurologist or technician. Quite the contrary, it should help explain how nuanced electroencephalogram can be, and why indiscriminate electroencephalogram is inappropriate. Some might argue not to teach nonexperts lest they overestimate their abilities or reach. We humbly submit that it is even more inappropriate to not know the basics of a test that is ordered frequently and resource intensive. We cover the characteristics of the "normal" electroencephalogram, electroencephalogram slowing, periodic epileptiform discharges (and its subtypes), burst suppression, and electrographic seizures (and its subtypes). Alongside characteristic electroencephalogram findings, we provide clinical pearls. These should further explain what the reporter is communicating and whether additional testing is beneficial. Along with teaching the basics and whetting the appetite of the general clinician, this resource could increase mutual understanding and mutual appreciation between those who order electroencephalograms and those who interpret them. While there is more to electroencephalogram than can be delivered via a single concise primer, it offers a multidisciplinary starting point for those interested in the present and future of this commonly ordered test.